The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1186/s12982-016-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing delivery practices of mothers over time and over space in Uganda, 2003–2012

Abstract: BackgroundIt is well known that safe delivery in a health facility reduces the risks of maternal and infant mortality resulting from perinatal complications. What is less understood are the factors associated with safe delivery practices. We investigate factors influencing health facility delivery practices while adjusting for multiple other factors simultaneously, spatial heterogeneity, and trends over time.MethodsWe fitted a logistic regression model to Lot Quality Assurance Sampling (LQAS) data from Uganda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…The small sample design of LQAS is based on the binomial distribution [ 26 ]. Prior studies suggest that LQAS is an efficient sampling design used when one wants to identify general program coverage or indeed communities having inadequate service coverage [ 27 – 29 ]. Therefore, in the context of the poorest and most remote districts of Zambia, LQAS was considered a suitable sampling design for evaluating the intervention because of the small sample size it requires for each cluster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small sample design of LQAS is based on the binomial distribution [ 26 ]. Prior studies suggest that LQAS is an efficient sampling design used when one wants to identify general program coverage or indeed communities having inadequate service coverage [ 27 – 29 ]. Therefore, in the context of the poorest and most remote districts of Zambia, LQAS was considered a suitable sampling design for evaluating the intervention because of the small sample size it requires for each cluster.…”
Section: Methodsmentioning
confidence: 99%
“…The segmentation sampling approach, advocated in survey guidelines was used as more rigorous second-stage sampling technique [ 29 , 30 ]. Once a reference house was selected, the next closest house was selected for an interview.…”
Section: Methodsmentioning
confidence: 99%
“…The women who had no education and basic education had greater odds of having a home delivery than those who had higher education. Other studies too have shown that institutional delivery is higher among educated people and those with better income status than the uneducated and poor [39][40][41]. This might be because educated women comprehend better about the potential risk associated with home delivery and have better idea about the service availability.…”
Section: Discussionmentioning
confidence: 97%
“…In both groups, economic status was also an important predictor of home delivery. Poverty is one of the key factors associated with low utilisation of health care services in Nepal and in other developing countries [39,40]. But very few women, both from marginalised and nonmarginalised (close to 2%) reported cost as the reason for not delivering in health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Although some countries are carrying out these surveys semiannually, 88 others do so annually or biennially. 89 Fragile countries experiencing conflict may have longer intervals due the higher costs and logistical challenges of carrying out a national survey in a humanitarian setting.…”
Section: (±38)mentioning
confidence: 99%